2019
DOI: 10.1002/jrs.5595
|View full text |Cite
|
Sign up to set email alerts
|

Lab‐on‐paper surface‐enhanced Raman spectroscopy platform based on self‐assembled Au@Ag nanocube monolayer for on‐site detection of thiram in soil

Abstract: A paper-based surface-enhanced Raman spectroscopy (SERS) substrate was prepared by assembling Au@Ag nanocubes onto a patterned paper with the assistance of a mask paper by liquid-liquid interface self-assembly techniques. The paper-based SERS substrate was glued to the glass slide to construct a novel lab-on-paper SERS platform. This paper-based SERS sensor possesses a sample injecting zone together with a SERS detection zone in order that sample pretreatment and detection could be performed simultaneously.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…For example, we and other research groups have demonstrated that the interfacial arrays can be transferred onto solid substrates, such as silicon wafers or quartz slides, by sliding the solid substrate material beneath the particles at a tilted angle and then carefully lifting the particle array out horizontally. [85][86][87][88][89][90] Similarly, it has been shown that arrays can be deposited onto the substrate material by placing the substrate at the bottom of the reaction vessel and then draining away the liquid phases. [40,[91][92] The biggest advantage of the physical deposition strategy lies in its versatility, which allows the nanoparticle arrays to be transferred onto almost any type of solid surface with ease, and the way in which the product material can combine the functionalities of both the 2D arrays and the solid substrates.…”
Section: Section 21 Transferring Soft-arrays Onto Rigid-substratesmentioning
confidence: 99%
“…For example, we and other research groups have demonstrated that the interfacial arrays can be transferred onto solid substrates, such as silicon wafers or quartz slides, by sliding the solid substrate material beneath the particles at a tilted angle and then carefully lifting the particle array out horizontally. [85][86][87][88][89][90] Similarly, it has been shown that arrays can be deposited onto the substrate material by placing the substrate at the bottom of the reaction vessel and then draining away the liquid phases. [40,[91][92] The biggest advantage of the physical deposition strategy lies in its versatility, which allows the nanoparticle arrays to be transferred onto almost any type of solid surface with ease, and the way in which the product material can combine the functionalities of both the 2D arrays and the solid substrates.…”
Section: Section 21 Transferring Soft-arrays Onto Rigid-substratesmentioning
confidence: 99%
“…Wang and co-workers designed a detection platform based on self-assembled Au@Ag nanocube (Au@Ag NCs) using a lab-onpaper SERS strategy for on-site detection of thiram residues in the soil (Figure 2D). [50] Au@Ag NCs with the average size of 53 nm were deposited onto filter paper via liquid-liquid interface self-assembly (LLISA) technology to form a paper-based SERS substrate with the assistance of a mask paper. The experimen-tal results showed that the paper-based SERS substrate exhibited outstanding quantitative ability to detect thiram in the soil, reaching a LOD of 0.148 mg kg −1 (Figure 2E).…”
Section: Eco-friendly Nanoplatforms For Pesticides Detectionmentioning
confidence: 99%
“…Paper-based SERS substrates have previously been prepared by drop-casting colloids onto paper surfaces or by dip-coating paper into colloids. [15][16][17]29,30 However, these methods typically lead to a very non-uniform distribution of nanoparticles on the substrate surface which results in relative standard deviations (RSD) of ca. 60%.…”
Section: Optimisation Of Sers-paper Filmsmentioning
confidence: 99%